Albumin-mediated alteration of plasma zinc speciation by fatty acids modulates blood clotting in type-2 diabetes. Issue 11 (5th February 2021) - Sobczak, Amélie I. S.; Katundu, Kondwani G. H.; Phoenix, Fladia A.; Khazaipoul, Siavash; Yu, Ruitao; Lampiao, Fanuel; Stefanowicz, Fiona; Blindauer, Claudia A.; Pitt, Samantha J.; Smith, Terry K.; Ajjan, Ramzi A.; Stewart, Alan J.
Abstract : Zn 2+ is an essential regulator of coagulation. In plasma, Zn 2+ availability is fine-tuned by human serum albumin (HSA). Here we show that elevated fatty acid levels contribute to altered coagulation in type-2 diabetes through Zn 2+ mishandling by HSA. Abstract : Zn 2+ is an essential regulator of coagulation and is released from activated platelets. In plasma, the free Zn 2+ concentration is fine-tuned through buffering by human serum albumin (HSA). Importantly, the ability of HSA to bind/buffer Zn 2+ is compromised by co-transported non-esterified fatty acids (NEFAs). Given the role of Zn 2+ in blood clot formation, we hypothesise that Zn 2+ displacement from HSA by NEFAs in certain conditions (such as type 2 diabetes mellitus, T2DM) impacts on the cellular and protein arms of coagulation. To test this hypothesis, we assessed the extent to which increasing concentrations of a range of medium- and long-chain NEFAs reduced Zn 2+ -binding ability of HSA. Amongst the NEFAs tested, palmitate (16 : 0) and stearate (18 : 0) were the most effective at suppressing zinc-binding, whilst the mono-unsaturated palmitoleate (16 : 1c9) was markedly less effective. Assessment of platelet aggregation and fibrin clotting parameters in purified systems and in pooled plasma suggested that the HSA-mediated impact of the model NEFA myristate on zinc speciation intensified the effects of Zn 2+ alone. The effects of elevated Zn 2+ alone on fibrin clot density and fibre thickness in a purified protein system were mirrored in samples from T2DM patients, who have derranged NEFA metabolism. Crucially, T2DM individuals had increased total plasma NEFAs compared to controls, with the concentrations of key saturated (myristate, palmitate, stearate) and mono-unsaturated (oleate, cis -vaccenate) NEFAs positively correlating with clot density. Collectively, these data strongly support the concept that elevated NEFA levels contribute to altered coagulation in T2DM through dysregulation of plasma zinc speciation.